Analyzing the Potential of Herbal Plant Research for Alzheimer's Disease in Diabetes: A Bibliometric Approach - Marzuki, Ahmad; Rahmayani, Almira; Khafi, Muhammad; Hertiani, Triana; Murwanti, Retno (Majalah Farmaseutik, 2024)
Alzheimer’s disease is a progressive neurologic dementia disorder and the fifth leading cause of death among elderly individuals. Its pathogenesis is closely linked to diabetes-induced brain insulin resistance, which accelerates beta-amyloid accumulation, exacerbating disease severity. This condition significantly impacts quality of life and healthcare costs, necessitating effective treatment strategies. Medicinal plants offer a promising avenue, with bibliometric analysis identifying trending active compounds for potential development as therapies for diabetic Alzheimer’s. This study analyzed 200 articles from the Scopus database, employing Scopus and VOSviewer 1.6.20 to visualize bibliometric trends by publication, country/territory, subject area, and keyword co-occurrence. Results indicate a recent decline in research activity, with China leading in publications across pharmacology, medicine, and biochemistry. Notably, flavonoids like “quercetin,” “kaempferol,” and “gallic acid” emerged as prominent topics.Keywords: Alzheimer’s diabetes, Bibliometrics, Herbal medicine, Extracts